2022
DOI: 10.1097/brs.0000000000004387
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Visits Can Generate Highly Accurate Diagnoses and Surgical Plans for Spine Patients

Abstract: Study Design. A Retrospective cohort study. Objective. To (1) assess whether diagnoses and surgical plans established during a new patient telemedicine visit changed following an in-person evaluation and (2) determine any differences in perioperative outcomes between patients who only had a telemedicine visit before surgery versus those who had a telemedicine visit followed by an in-person evaluation before surgery. Summary of Background Data. Data on capability of telemedicine to deliver high-quality preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Telehealth may be particularly effective for the management of patients with spine disorders who have both advanced imaging and appropriate patient history available, including determining interventional procedures and spine surgery 89 . This is supported by a consistency of recommendations and minimal differences between telehealth and an in‐person visit used to determine a procedural or surgical plan 90‐95 . Use of telehealth has been shown to result in high physician confidence to develop treatment plans, 96,97 high patient satisfaction 98‐100 particularly for follow‐up visits 101 and management of low back pain, 102 including exercise programs 103 …”
Section: Concussion Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Telehealth may be particularly effective for the management of patients with spine disorders who have both advanced imaging and appropriate patient history available, including determining interventional procedures and spine surgery 89 . This is supported by a consistency of recommendations and minimal differences between telehealth and an in‐person visit used to determine a procedural or surgical plan 90‐95 . Use of telehealth has been shown to result in high physician confidence to develop treatment plans, 96,97 high patient satisfaction 98‐100 particularly for follow‐up visits 101 and management of low back pain, 102 including exercise programs 103 …”
Section: Concussion Recommendationsmentioning
confidence: 99%
“…89 This is supported by a consistency of recommendations and minimal differences between telehealth and an in-person visit used to determine a procedural or surgical plan. [90][91][92][93][94][95] Use of telehealth has been shown to result in high physician confidence to develop treatment plans, 96,97 high patient satisfaction [98][99][100] particularly for follow-up visits 101 and management of low back pain, 102 including exercise programs. 103 Although studies are currently limited on telehealth use for evaluating how a patient reports treatment response following the use of procedures to alleviate pain, applications of telehealth visits compared to inperson visits have been evaluated in the management of chronic pain conditions of Achilles tendinopathy and plantar fasciitis.…”
Section: Management Of Spine Disorders and Painmentioning
confidence: 99%
“…However, due to the time-sensitive nature of certain spinal pathologies, the spine service has remained relatively more active than other orthopaedic specialties, even during the initial peak of the pandemic and its associated restrictions ( 3 ). Spine surgeons have a critical role in the pandemic to identify and still treat patients with urgent and emergent spinal conditions while attempting to minimize resource utilization as feasible ( 4 ). Despite the widespread surgery cancellations, care was largely continued for patients presenting with progressive neurological deficits, myelopathy with spinal cord at risk, spine trauma with instability, or cauda equina syndrome ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is mounting evidence showing that video-based diagnostic evaluation and decision-making have now reached an acceptable level of accuracy, making them suitable for adoption in orthopaedic surgery. 7,11,26-28…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is mounting evidence showing that video-based diagnostic evaluation and decisionmaking have now reached an acceptable level of accuracy, making them suitable for adoption in orthopaedic surgery. 7,11,[26][27][28] Looking beyond the field of surgery, Hersh et al, 29 in their systematic review, found telemedicine to be effective in specialities where verbal interactions form a key component of patient assessment, such as psychiatry and neurology. This suggests it has equal suitability for the management of chronic orthopaedic conditions, where such dialogue is equally pivotal.…”
Section: Introductionmentioning
confidence: 99%